CROSS-LINGUISTIC TYPOLOGY AND ITS ROLE IN ENHANCING LANGUAGE LEARNING AND TRANSLATION COMPETENCE (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
original article investigates the fundamental significance of cross-linguistic typology in strengthening language learning strategies and advancing translation competence. It reinterprets major typological classifications—phonological, morphological, syntactic, semantic, and pragmatic typology—and highlights their practical value for learners and translators. The article demonstrates that typology functions not only as a descriptive branch of linguistics but also as an essential methodological tool for multilingual education, contrastive error analysis, and translator training.